The resolvent kernal $R(x,t,\lambda)$ for the Volterra integral equation $$\phi(x)=x+\lambda\int\limits_a^x\phi(s)ds$$ is $\begin{array}1 1. e^{\lambda(x+t)} && 2. e^{\lambda(x-t)} && 3. \lambda e^{(x+t)} && 4. e^{\lambda xt} \end{array}$

From what I learned from here: Find iterative kernel and then try guess resolvent kernel, $R=\sum\limits_{i=1}^\infty K_i(x,t)$

Comparing with general form of Volterra equation of second kind, $$g(x)\phi(x)=f(x)+\lambda\int\limits_a^x K(x,t)\phi(t)dt$$

Kernel, $K(x,t)=1,K_1(x,t)=K(x,t)=1$

Now, $K_2(x,t)=\int\limits_t^x K(x,s)K_1(s,t)ds=\int\limits_t^x ds=x-t$

$K_3(x,t)=\int\limits_t^x K(x,s)K_2(s,t)ds \\=\int\limits_t^x (s-t)ds=\frac{s^2}2-ts\big|_{s=t}^x \\=\frac{x^2}2-tx-\frac{t^2}2+t^2=\frac{x^2}2-tx+\frac{t^2}2 \\=\frac1{\sqrt2}(x-t)^2$

And I am stuck, though I am tempted to choose option 2, since it has $x-t$.

I haven't done any coursework in Integral Equations, and I know only bits and pieces about it.

My doubts are:

  1. Was I right in choosing $K(x,t)=1$? How does $\lambda$ find its place in resolvent kernel?
  2. How to proceed further?
  3. Are there any trial and error methods, where I can plug in the options to see if it is the answer?

It is better to start with the definition: $R(x,t,\lambda)$ is the resolvent kernel for $\phi(x)=f(x)+\lambda\int\limits_a^x\phi(s)ds$ if the solution can written as $$ \phi(x) = f(x) + \lambda\int_a^x R(x,t,\lambda)f(t)dt. $$ Taking derivatives on both sides of the equation $\phi(x)=x+\lambda\int\limits_a^x\phi(s)ds$, we get $\phi'(x) = f'(x)+\lambda \phi(x)$. Therefore, $$ \frac{d}{dx}e^{-\lambda x}\phi(x) = e^{-\lambda x} f'(x) $$ and \begin{align} e^{-\lambda x}\phi(x) &= e^{-\lambda a}\phi(a) + \int_a^x e^{-\lambda t}f'(t)dt\cr &=e^{-\lambda a} \phi(a)+\left.e^{-\lambda t}f(t)\right|_a^x -\int_a^x f(t)de^{-\lambda t} \cr &=e^{-\lambda x}f(x)+e^{-\lambda a}\big(\phi(a)-f(a)\big) +\lambda \int_a^x e^{-\lambda t}f(t)dt. \end{align} Using the fact $\phi(a)=f(a)$ (by evaluating the integral equation at $x=a$), we get $$ \phi(x) = f(x)+\lambda\int_a^x e^{\lambda (x-t)}f(t)dt. $$ Therefore the resolvent kenrel is $R(x,t,\lambda)=e^{\lambda(x-t)}$.

If you continue your calculation, you will find (using induction) $K_n(x,t) = (x-t)^{n-1}/(n-1)!$, and the connection to the resolvent kernel is that $$ R(x,t,\lambda) = K_1(x,t)+\lambda K_2(x,t) + \lambda^2 K_3(x,t)+\cdots =e^{\lambda(x-t)}, $$ consistent with the above approach.

  • $\begingroup$ Thanks a lot! That explains it! I made a small calculation mistake as well! And proper definition of resolvent kernel is what I missed! Will launch the bounty tomorrow! $\endgroup$ – Jesse P Francis Jan 23 '16 at 4:41
  • $\begingroup$ Also, resolvent kernel, $R(x,t,\lambda)=\sum\limits_{i=1}^\infty \lambda^i K_i(x,t)$, I missed $\lambda$! $\endgroup$ – Jesse P Francis Jan 23 '16 at 4:51
  • 1
    $\begingroup$ Thanks. That's very generous of you. $\endgroup$ – yhhuang Jan 26 '16 at 9:31
  • $\begingroup$ not planning to cross the 500rep mark (again) any time soon, so if you find any posts worth a bounty/attracting attention to, do tell me! It's free give away! :) $\endgroup$ – Jesse P Francis Jan 26 '16 at 11:29

This is not a direct answer to the question which wording and notations seem not clear. Nevertheless, the analytic solution of the integral equation $\phi(x)=x+\lambda\int\limits_a^x\phi(s)ds$ is given below. Hoping this will help you to choose the right option. $$\frac{d\phi}{dx}=1+\lambda \phi(x)$$ The general solution of this linear ODE is : $$\phi(x)=-\frac{1}{\lambda}+c\:e^{\lambda x}$$ Bringing it back into the integral equation leads to :

$-\frac{1}{\lambda}+c\:e^{\lambda x}=x+\lambda\int\limits_a^x \left(-\frac{1}{\lambda}+c\:e^{\lambda s} \right)ds = a+c e^{\lambda x}-c\:e^{\lambda a}$

$c=\left(a+\frac{1}{\lambda}\right)e^{-\lambda a}$

$$\phi(x)=-\frac{1}{\lambda}+\left(a+\frac{1}{\lambda}\right)\:e^{\lambda (x-a)}$$

  • $\begingroup$ This is the approach that comes naturally to me when I see this integral equation. I am curious how one would recover the form of the accepted solution from your last step -- surely it's not coincidental that the Resolvent kernel is in the solution, but I can't seem to reconcile the two equalities in a way that is natural. I realize this is about 2 years too late :). $\endgroup$ – David Kozak Dec 4 '17 at 2:16

Your aswer is also right. Instead of getting $(x-t)^2\over\sqrt2$, you will get $(x-t)^2\over2$. Simililarly $K_4$ can be find and when we generalize it , it will will be series of $exp(x-t)$

  • $\begingroup$ You have contributed nothing new to an old question first having answers $\endgroup$ – Shailesh May 30 '16 at 9:07
  • $\begingroup$ @Sailesh, what he mentioned is correct! I had mentioned it in once of the comments above. $\endgroup$ – Jesse P Francis Jun 6 '16 at 6:13

Your way of finding the Resolvent Kernel is also correct. There is a slight mistake in calculating $K_3(x,t)$. $$K_3(x,t)=\frac{(x-t)^2}{2!}$$$$K_4(x,t)=\frac{(x-t)^3}{3!}$$ and so on.

And about the final series to get the Resolvent Kernel, it should be $$R=\sum\limits_{i=1}^{\infty} \lambda^{i-1} K_i(x,t).$$ SO $R=1+ \lambda (x-t)+\frac{\lambda^2(x-t)^2}{2!}+\frac{\lambda^3(x-t)^3}{3!}+\dots=e^{\lambda(x-t)}.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.